Tourism and Development: De/Constructing Discourse - Thapa, Roshan (The Gaze: Journal of Tourism and Hospitality, 2018)
This article is an outgrowth of an odyssey of more than a decade to the very popular touristic destinations of Nepal, namely Ghale Gaon, Sirubari and Bandipur, and disciplinarily synergetic in my act of knowing and representing- the objectivities and the subjectivities emerging in tourist-host interaction, the public discourses, and the ways these have shaped these destinations today- my primary concern in this article. Today, these destinations, which would perhaps remain virgin, development and otherwise, are at threshold, vividly manifesting array of changes in every spheres of living in with their adherence to village tourism in the name of development per se modernization, the camelian evolution if not reinstate on time with pragmatic tourism paradigm to my anticipation these destination will not thrive to attack tourists as of today and consequently thwart development in true sense With this conscientization, by focusing on the effects of tourism and new ways of sensing tourism and development this article proposes an alternative episteme in tourism and development analysis with special reference of these destinations In my attempt to do justice to the era to which I belong, as a devotee of post-modernism centripetal to undertaking this task were the postulates of social constructivism and “(N)One Paradigmatic Research Design”, at my disposal. I am hopeful that this paper contributes to the deficit of knowledge in relating concepts and theories to what I termed as anthropic development. The Gaze: Journal of Tourism and Hospitality Vol.9 2018 p.1-22